GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 1058 species occurrences available in GBIF matching the query: TaxonKey: Oryza latifolia Desv. HasCoordinate: true. The dataset includes 1058 records from 39 constituent datasets: 2 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 1 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 64 records from The System-wide Information Network for Genetic Resources (SINGER). 4 records from Repatriación de datos del Herbario de Arizona (ARIZ). 1 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 17 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 17 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 38 records from Instituto de Botánica Darwinion. 1 records from PRECIS. 2 records from Plantas Acuáticas de la Orinoquía Colombiana. 344 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 13 records from Flora Novo Galiciana-Gramineae. 200 records from Missouri Botanical Garden. 53 records from herbario. 39 records from MEXU/Colección de Plantas Acuáticas. 3 records from Rio de Janeiro Botanical Garden Herbarium Collection. 4 records from Herbier de la Guyane. 2 records from Herbarium of The New York Botanical Garden. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 92 records from Especímenes INBio. 3 records from Nationaal Herbarium Nederland. 4 records from United States National Plant Germplasm System Collection. 5 records from Geographically tagged INSDC sequences. 12 records from The AAU Herbarium Database. 3 records from UA Herbarium. 39 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Instituto Nacional de Pesquisas da Amazônia (INPA) - Herbarium. 13 records from NMNH occurrence DwC-A. 1 records from Digital Florula - Palo Verde Biological Station. 2 records from MEXU/Plantas Vasculares. 4 records from Natural History Museum (London) Collection Specimens. 2 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 7 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 3 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from Herbario Amazónico Colombiano. 1 records from Marie-Victorin Herbarium (MT). 49 records from SINGER Coordinator. 8 records from Instituto de Ciencias Naturales. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens.
Keywords: GBIF; biodiversity; species occurrences